Peran Dan Fungsi Telaah Kurikulum Merdeka - Desi Suryati; Dewi Puspita Sari; Kantri Nurlisa; Mustafiyanti Mustafiyanti (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The Merdeka Curriculum is a new breakthrough in the education system in Indonesia which gives schools and teachers greater autonomy in designing learning. This requires a comprehensive curriculum review to ensure that the implementation of the Independent Curriculum runs in accordance with the goals and expectations. This scientific journal aims to examine the role and function of independent curriculum studies. Independent curriculum review is defined as a systematic and planned activity to study, analyze and evaluate the implementation of the Independent Curriculum in schools. Reviewing the independent curriculum is a shared responsibility between education stakeholders at the school level, including school principals, teachers and school committees. By conducting continuous reviews of the Independent Curriculum, it is hoped that the implementation of the Independent Curriculum can achieve its goal of producing the nation's next generation who have faith, noble character, knowledge and skills that are in line with the needs of the times.